“Youth 2.0 project”: Multi-professional Intervention to Protect Adolescents from NPS and Other Drug Use - V. Rapaccini; S. Biscontini; A. Molinaro; G.P. Di Loreto; A. Pasini; O. Corazza; A. Metastasio (Emerging Trends in Drugs, Addictions, and Health)
Introduction: The COVID 19 pandemic has significantly affected the consumption of drugs determining a substantial increase in psychiatric discomfort and mental illness, especially among youth. Our study focuses the attention on Terni, a city in the center of Italy, actually defined by journalists as “the black heart of drug dealing in Umbria”: in fact, according to the Central Directorate for Drug Services report, in this city more than half of the drug related deaths of Umbria are registered; in addition, more than 60% out of hashish, cocaine and heroin detected in Umbria are seized in Terni. To cope with these emerging challenges, the “Youth 2.0” Project in Terni, a city in the center of Italy heavy affected by the drug problem, aimed to provide a personalized tailored interventions for young people aged between 14-24 years old suffering from mental illness, psychiatric disorders, psychological distress and a wide range of substance/non-substance related forms of addictions in specific semi residential centers. The project, which involved schools-based intervention, group meetings and family meetings, clinical screenings among others, was implemented with the support of the families, law enforcement agencies, the Usl Umbria 2 Addiction Department and Child Neurodevelopmental Disorder Centre. The aim of our study is to evaluate the impact of such project on the intake of illegal substances among this cohort. Methods: Retrospective analysis of the clinical data collected by Usl Umbria 2 Addiction Department concerning adolescents between 14 and 24 years old and comparison between those involved/not involved in the “Youth 2.0” Project during 2019-2022. Results: A general increase in substance addictions rate (smoking, alcohol, drugs) was recorded. The consumption of illegal substances (in particular cannabinoids) grew of almost 10% (from 58% in 2019 to 64% in 2022). In addition, novel trends of substance misuse were also identified. Whereas heroin and cocaine were the most widespread substances, NPS, expecially cannabinoids, remained the preferred drug of choice in the population under 20 years of age. For what concern Youth 2.0 project, we noticed a significant decrease in cannabinoids use among adolescents in charge at the Usl Umbria 2 Addiction Department (from 3.9% in 2019 to 2.9% in 2022) with a parallel exponential growth (from 1.3% in 2019 to 5.2% in 2022) in adolescents monitored with Youth 2.0 Project. Conclusions: Findings confirms the crucial importance of identifying and promoting appropriate intervention strategies in collaboration with various stakeholders (families, schools, police, clinical staff) to reduce the substance intake among young people. Considering also the function of self-care medication that some adolescents attribute to cannabinoids, these preliminary data lead us to assume that the “Youth 2.0 Project” provided a valid alternative to drug consumption especially for what concerns cannabinoids and derivatives.